Perkaitan faktor organisasi dengan motivasi kerja:|bkajian di kalangan pekerja sokongan. - Florialyeen, ak Sangok. (Universiti Malaysia Sarawak (UNIMAS), 1999)
The purpo.\'e of this stlldy is to determine the correlation of organizational factor.\' with work motivation level and also to determine the level o/work motivation among the slIpporting staff CMS Cement Sdn. Bhd. Questionnaires were circulated to get Jeedbacl.: Fom 80 slIpporting staff Data ohtained were analyzed IIsing descriptive and inferential .\'tatistics inclllding Pearson Correlation Coeeficient. Independent t-test and One-Way ANOVA. Findings showed that the supporting staffhave a high level of work motivation. Orginazational factors mch as joh (r :0.27. p = 0.01) is positive correlated significantly with work motivation bllt relationship with is weak Also work group. is positively correlated Significantly with work motivation (r ~ (J.5.1. p = 0.00) and the relation is moderately strong Other organizational factors sllch as SIIpervision (r = 0. 12. P = 0.30) and rewards (r = 0.17. P = 0.13). is not significantly correlated with work motivation. T-test and One Way ANOVA showed that there is no significant differences of the level of work motivation based on the demography factors such as gender. age. qllalification level and numher ofyears working with the organization. The implication ofthis research indicates that there is a correlation of organizational factors such as job and work group with the level ofwork motivation.